Girls Get WISE—A programming model for engaging girls+ in STEM - Franz-Odendaal, Tamara A.; Marchand, Sally (Frontiers in Psychology, 2022)
The majority of STEM disciplines in Canada are male-dominated and there is a significant lack of programming available to girls. The Girls Get WISE program is a university-based program that is funded by federal government, the university and corporate sponsorship. This program is delivered in person by educational professionals, science students and past participants. By engaging girls in hands-on interactive STEM activities in a safe and fun space, this program provides an opportunity for young women to showcase their talents and excitement for science-based topics. The features of this program and its evaluation over a ten year period are described here.